How implicit self-esteem influences perceptions of self-esteem at zero and non-zero acquaintance - Giacomin, Miranda; Jordan, Christian H. (My University, 2016)
People’s perceptions of others’ self-esteem correspond with others’ explicit self-esteem. We test whether implicit self-esteem also affects perceptions of self-esteem at zero and non-zero acquaintance. Targets completed measures of implicit and explicit self-esteem, had photographs taken, and completed self-related interviews. Unacquainted perceivers rated targets’ self-esteem after viewing varying degrees of information about targets (Study 1) or preselected high and low implicit self-esteem targets (Studies 2 and 3). When perceivers viewed photographs, only target explicit self-esteem predicted self-esteem ratings. However, when perceivers read targets’ interview transcripts, both target explicit and implicit self-esteem predicted self-esteem ratings. When targets described sensitive information, their apparent comfort and self-certainty were associated with ratings of their self-esteem. These cues, moreover, were valid indicators of implicit self-esteem.
Keywords: implicit self-esteem; zero acquaintance; explicit self-esteem; person perception